INFLUENCE OF FINANCIAL ATTITUDE AND FINANCIAL KNOWLEDGE ON FINANCIAL BEHAVIOR WITH LOCUS OFCONTROL AS AN INTERVENING VARIABLE - Fran’s Gidion Sinuhaji; Isfenti Sadalia; Syahyunan (CV. Radja Publika, 2024)
This study aims to determine the influence of Financial Attitude and Financial Knowledge on Financial behavior through Locus of Control as an intervening variable. This study is associative research and the type of data used is quantitative data. The Data used were obtained from primary data and secondary data. The method of analysis used is descriptive statistical analysis and structural equation modeling. Population and sample in this study amounted to 353 students of Methodist University of Indonesia with sampling technique used is purposive sampling. The results of this study showed that Financial Attitude has a positive and significant effect on Financial behavior in students of Methodist University Indonesia, Financial Attitude has a positive but insignificant effect on Locus of Control in students of Methodist University Indonesia, Financial Knowledge has a positive and significant effect on Financial behavior in students of Methodist University Indonesia, Financial Knowledge has a, Locus of Control has a positive and significant effect on Financial behavior in students of Methodist University of Indonesia, Locus of Cotrol is not able to mediate the relationship of Financial Attitude to Financial behavior but is able to mediate the influence of Financial Knowledge on Financial behavior.